Organization and diagnostics of future psychologists individual work in the process of study science subjects disciplines at higher educational institutions - Bilyk, Valentyna (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2017)
The article investigates the problem of organization and diagnostics the individual work of future psychologists in the process of study science subjects in higher educational institutions. The author analyzes balance between students’ individual work and classroom hours in training science disciplines for future psychologists in M. P. Dragomanov NPU. Taking into account set by the curriculum amount of hours and the necessity of constant control over the students’ individual work it was substantiated in the article the reasonability of innovative educational technologies use (individual research projects, multimedia presentations, portfolios, computer testing), the use of which, the author states, would help effectively manage and control the individual work of future psychologists in the process of study science subjects.